ANALISIS IKLAN DAN ENDORSER TERHADAP PEMBENTUKAN BRAND AWARENESS SERTA DAMPAKNYA PADA KEPUTUSAN PEMBELIAN PRODUK KECAP MANIS ABC - Raih Nur Fatmayanti, Susy; Yoestini, Yoestini (Diponegoro Journal of Management, 2012)
ABC products was an old brand that had a good quality. ABC always improve their quality products trought the age and had an international standardized. This purpose of this research is to analyze the impact of the advertising and endorser towards brand awareness and their effects towards decision buying on ABC soy sauce, where  independents variables of this research is Advertising (X1), Endorser  (X2), and Brand Awareness (X3) become intervening variable that give impact towards Buying Decision (Y) as a dependent variable. The population of this research is soy sauce customer. Sample that used in this research are 100 respondents. Technique sampling method that used in this research is purposive sampling. While its survey method used questionnaires. Then analyzed method that used in this research includes validity test, reliability test, multiple regressions, and classical assumption test. Hypothesis test that used includes F test, t-test, and Determination Coefficients Analysis (R²). According to this research results, regression formula: Y1 = 0,45 X1 +  0,8 X2 and = 0,661 + 0,140.  According to statistic data analysis, indicators in this research showed that all data were valid and reliable. As an individual, variable that have the biggest impact is Brand Awareness. And followed by its independent variable, Advertising, and Endorsers. Hypothesis testing used t-test showed that the advertising significantly influences its dependent variable  (Brand Awareness), but Endorser has no significant impact towards Brand Awareness. When this research used multiple regression analysis, Brand Awareness significantly impact Buying Decision.